The influence of Vico’s and Hegel’s ideas on the Risorgimento. De Arcangelis, A. (2025). Vico, Hegel, and the Making of Modern Italy. The Spirit of the Risorgimento. London: Bloomsbury. - Ivashchenko, Ivan (Sententiae, 2025)
Review of De Arcangelis, A. (2025). Vico, Hegel, and the Making of Modern Italy. The Spirit of the Risorgimento. London: Bloomsbury.